Microstructure and texture of CoCrNi medium entropy alloy (MEA) processed by severe cryo-rolling: A study vis-a-vis cold-rolling. (November 2021) - Saha, J.; Saha, R.; Malladi, S.R.K.; Bhattacharjee, P.P.
Abstract: The microstructure and texture of severely cryo-rolled and annealed CoCrNi equiatomic medium entropy alloy (MEA) were investigated in the present work. To highlight the impact of cryo-rolling, these aspects were critically compared with similarly cold-rolled and annealed MEA. The alloy was cryo- and cold-rolled to 90% reduction and annealed at temperatures ranging from 700 °C to 1200 °C. Formation of deformation-induced nanostructure was observed in both materials. However, the slightly higher hardness of the cryo-rolled material was indicative of finer nanostructure and higher defect density as compared to those in the cold-rolled material. The cold-rolled material showed a perceptibly stronger brass texture than the cryo-rolled alloy. Extreme grain refinement and high density of intersecting shear bands appeared to weaken the brass texture in the cryo-rolled material. The lower grain size in the cryo-rolled material after different annealing treatments was consistent with a greater density of potential nucleation sites. The annealing texture of both cryo- and cold-rolled materials showed the presence of weak α-fiber (ND//<110>) components. Annealing resulted in a pronounced decrease in hardness, although sufficiently high hardness could still be obtained at a lower annealing temperature regime. Moreover, the hardness results were represented in a Hall-Petch plot which revealed a very high lattice friction stress for the MEA. Highlights: Effect of cryo-rolling was compared with cold-rolling in CoCrNi MEA. Nanocrystalline structure with higher hardness in the cryo-rolled MEA. Weaker brass texture in the cryo-rolled MEA. Consistently smaller grain size in the cryo-rolled MEA after annealing. Weak recrystallization texture and high lattice friction stress were established.